2022
DOI: 10.1136/bmjopen-2021-058649
|View full text |Cite
|
Sign up to set email alerts
|

High HDL-C and high LDL-C are risk factors of pterygium in a population-based cross-sectional study in Southern China: the Dongguan Eye Study

Abstract: ObjectivesTo investigate the relationship between serum lipids and pterygium in a large-scale rural population aged 40 years or older from Southern China.Study designThe Dongguan Eye Study was a cross-sectional population-based study from September 2011 to February 2012.SettingThe area was set in the rural area of Dongguan, Southern China.ParticipantsAdult rural population aged 40 or older.MethodsParticipants underwent physical, haematological and ophthalmic examinations.Primary and secondary outcome measuresT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…HDL-C can directly regulate glucose metabolism and results in its antidiabetic effects. Current evidence has suggested that high HDL-C concentrations are risk factors for infectious diseases, pterygium, end-stage renal disease (ESRD) in lupus nephritis, increased insulin resistance in metabolic syndrome, and all-cause mortality [ 5 , 10 13 ]. Accordingly, a U-shaped relationship between HDL-C levels and cardiovascular and cancer mortality has been plotted [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…HDL-C can directly regulate glucose metabolism and results in its antidiabetic effects. Current evidence has suggested that high HDL-C concentrations are risk factors for infectious diseases, pterygium, end-stage renal disease (ESRD) in lupus nephritis, increased insulin resistance in metabolic syndrome, and all-cause mortality [ 5 , 10 13 ]. Accordingly, a U-shaped relationship between HDL-C levels and cardiovascular and cancer mortality has been plotted [ 14 ].…”
Section: Introductionmentioning
confidence: 99%